2013
DOI: 10.1186/1756-0500-6-73
|View full text |Cite
|
Sign up to set email alerts
|

De novo transcriptomic resources for two sibling species of moths: Ostrinia nubilalis and O. scapulalis

Abstract: BackgroundThis study aimed at enhancing the transcriptomic resources for two sibling species of moths, Ostrinia scapulalis (Adzuki bean borer) and Ostrinia nubilalis (European corn borer), as a foundation for future researches on their divergence history. Previous works on these species had shown that their genetic divergence was low, while they were reproductively isolated in natura and specialized on different host plants. Comparative genomic resources will help facilitate the understanding of the mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The rapid development of next-generation sequencing, such as Illumina sequencing, has provided cost-effective methods for the transcriptomic characterization of insect species that lack a fully-sequenced genome. Many insects have been sequenced, including the ACB 12 13 14 15 and its sibling species, the European corn borer 16 17 . The deeper sequencing coverage of Illumina sequencing combined with de novo transcriptome assembly will facilitate the characterization of genes in the absence of a reference genome.…”
mentioning
confidence: 99%
“…The rapid development of next-generation sequencing, such as Illumina sequencing, has provided cost-effective methods for the transcriptomic characterization of insect species that lack a fully-sequenced genome. Many insects have been sequenced, including the ACB 12 13 14 15 and its sibling species, the European corn borer 16 17 . The deeper sequencing coverage of Illumina sequencing combined with de novo transcriptome assembly will facilitate the characterization of genes in the absence of a reference genome.…”
mentioning
confidence: 99%
“…Further comparative analysis of the reference transcripts with the Lepbase [23] reference protein set detected probable homologs for 20,835 transcripts. OHR analyzes [12] on the best matches indicated that 61% of the CDS were reconstructed at least at 60% of the corresponding reference lepidopteran protein homolog, whereas 43% of the transcript CDS were assembled at full length.…”
Section: Experimental Design Materials and Methodsmentioning
confidence: 99%
“…To further investigate the host adaptation and divergence between these two sibling species at a pangenomic scale, we have elaborated new genomic and transcriptomic resources consisting of an OSCA draft genome and a related reference transcriptome. The latter extends a published transcriptomic set generated with Roche 454 sequencing technology [12] .…”
Section: Datamentioning
confidence: 99%
“…First, we applied default parameters and the normalization procedure of the Trinity package (version r20140413p1 [ 28 ]) to assemble high quality reads of the 12 ECB libraries and of the 12 ABB libraries separately into two comprehensive transcriptomes. Then, for each of the resulting ECB and ABB assemblies, we included a 454 de novo transcript set previously obtained by Gschloessl et al [ 27 ] from four ECB and four ABB adults, respectively. Such meta-assemblies that combine different technologies of sequencing reads have been proved to increase contig length and coverage in other studies [ 50 , 61 ].…”
Section: Methodsmentioning
confidence: 99%